The concept of an automated educational system for the training of refueling complexes personnel - P. I. Klimov; V. M. Samoylenko (Научный вестник МГТУ ГА, 2020)
At present the aviation fuel supply industry is characterized by complex technological processes, in which possible incidents and accidents can lead to economic and environmental losses. These processes require highly qualified and specially trained engineering and technical personnel. The rapid development of digital technologies and their implementation in the technological processes for ensuring flights of aircraft aviation fuel, such as continuous monitoring of fuel cleanliness, the quantity and consumption records of aircraft aviation fuel using automated systems, as well as the use of new equipment, such as mass meters, which are highly accurate. All this requires a new approach to the training of the refueling complexes personnel. In addition, the development of refueling complexes is on the way to optimize the operations. So, for example, the responsibilities of the aircraft refueling operator are also assigned to the driver of the refueling tanker. Currently, the technical facilities of the warehouse and refueling complex equipment used for aircraft refueling are included as part of the airport infrastructure in order to ensure the flights regularity. Application of the new equipment using digital technologies is associated with improving the quality of refueling operations at all stages of aviation fuel supply. To ensure effective management of aviation fuel supply processes at all stages, the organizational structure should be based not only on modern equipment of all parts of the technological chain of fuel preparation, but also on a closed automated control system based on the introduction of modern, intelligent control and measuring devices. In these conditions, the issue of training personnel of fueling complexes becomes relevant. The solution to this issue is in the development of automated training systems, that allow to accelerate staff training and reduce the cost of training. Therefore, the article discusses the structural and functional model of an automated training system (ATS) that combines disparate solutions and forms a new system for solving problems of training, certification and information support for personnel of aviation fuel supply organizations (AFSO). The proposed training system allows training not only for one workplace, but taking into account individual characteristics, for example, to prepare both the driver of the vehicle and the refueling operator in one person. The article describes the scenarios of the use of ATS subsystems developed in the work, which determine the basic functional composition. In conclusion, based on the developed scenarios for the use of subsystems, the developed structural and functional model of the ATS is presented, which provides solutions to the problems of maintaining the operation of the AFSO and supporting decision-making.